EJCR 2020
DOI: 10.31487/j.ejcr.2020.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Hydatic Cyst: An Unusual Cause of Heart Failure

Abstract: Pericardial hydatic cyst is rare even in endemic countries. We report a case of 69-year-old man with isolated pericardial hydatid cyst that presented an overall heart failure. Tran thoracic echocardiography and computed tomography are revealed the pericardial cystic mass. Surgical cystectomy was realized without cardiopulmonary bypass. In post-operative the patient received albendazole. He remained asymptomatic without recurrence during 18 months follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In our study, the chest X-ray revealed an enlarged cardiac silhouette with a water bottle configuration and haziness in bilateral costophrenic recesses. Hyper-eosinophilia may be found in only 20%-30% of the cases, in case of invasion or rupture of the cyst [20] . Serological tests like the Casoni test are not very reliable.…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the chest X-ray revealed an enlarged cardiac silhouette with a water bottle configuration and haziness in bilateral costophrenic recesses. Hyper-eosinophilia may be found in only 20%-30% of the cases, in case of invasion or rupture of the cyst [20] . Serological tests like the Casoni test are not very reliable.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Notably, superficial cysts can be excised with a beating heart, as demonstrated in our patient's case. Employing resection under cardiopulmonary bypass has demonstrated significant utility in conducting comprehensive assessments of both myocardial and pericardial conditions [20] . In our study, the patient received albendazole therapy 3 months before the surgery.…”
Section: Clinical Discussionmentioning
confidence: 99%